Penerapan Triple Bottom Line Pada PT Bank Rakyat Indonesia Tbk - Fara Brygita Ramadhani; Cholis Hidayati (Akuntansi, 2024)
This research analyzes the implementation of the Triple Bottom Line (TBL) concept by PT Bank Rakyat Indonesia (BRI) in their 2022 sustainability report, using a qualitative descriptive analysis method. The TBL concept, encompassing "People," "Planet," and "Profit," has become a central focus in various business sectors, emphasizing the importance of social, environmental, and financial sustainability. The findings reveal that BRI has successfully led the way in implementing TBL in the Indonesian banking sector, with positive impacts on society and the environment, alongside robust financial growth. This study provides a profound understanding of BRI's application of the TBL concept, serving as inspiration for other companies to follow suit in maintaining a balance between "People," "Planet," and "Profit."